Upaya Rehabilitasi Korban Penyalahgunaan Narkotika dan Obat Adiktif (Narkoba) - Fransisca, Retno Devi; Sidiq, Mahfudz (University of Jember, 2019)
Abstract Drug abuse is a problem that is no longer public. Drug abuse in Lumajang District ranked 9th in East Java. Based on the year 2015 the number of drug abuse victims in the district was 566 people. National Narcotics Agency (BNNK) Lumajang is an institution that provides rehabilitation services for victims of drug abuse. In 2016 BNNK handled 80 patients, in 2017 there was 57 patients, and 23 patients in 2018. The efforts that were carried out to restore victims of narcotic abuse and addictive drugs (drugs). The problem of this study was how to attempt the rehabilitation of drug victims and addictive drugs (drugs) in the BNN of Lumajang district. The study used a qualitative approach with descriptive type. Determination of informant with Purposive technique. Data collection techniques using non-participant observation, semi-structured interviews, and documentation. Data analysis techniques using data reduction, data display, and verification. The validity technique of data uses the source and method triangulation. The result of research on rehabilitation efforts is to build relationships with clients, conduct assessment, intervene by determining the plan of therapy and counseling, monitoring and termination.